ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI TERPADU (SISTER) MENGGUNAKAN METODE END USER COMPUTING SATISFACTION DI SMK N 2 KECAMATAN GUGUAK - Nandi Pinto Setiawan; Muhammad Anwar; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
This research is aimed to describe user’s satisfaction regarding information system applied at SMKN 2 KEC GUGUAK. Appleying EUCS method and its effects on users’ satisfaction of integrated information system are analysed by contribution or determinan factors. By using Survey technique, this study was conducted to 434 users as the population. Respondents or sample were selected by propotional stratified random sampling as many 81 users. However, the study result have shown that content variable, accuracy, format, easy of use,  and timelineness are simultaneously affecting the users’ satisfaction variable and giving contribution significantly of 82,2 %. It means that improving many factors as above will absolutely increase the quality and users’ satisfaction of integrated information system as well.Keywords: End User Computing Satisfaction (EUCS), User Satisfaction, Integratet Information System.